Lactobacillus fermentum PS150 showed psychotropic properties by altering serotonergic pathway during stress. (August 2019) - Liu, Yen-Wenn; Ong, Jia Sin; Gan, Chee Yuen; Khoo, Boon Yin; Yahaya, Sawibah; Choi, Sy Bing; Low, Wai Yee; Tsai, Ying-Chieh; Liong, Min Tze
Graphical abstract: Highlights: Psychotropic effects of PS150 was investigated in a chronic mild stress rats model. Rats fed with PS150 showed improved cognition and memory. PS150 reversed the decrease of serotonin and elevation of indoleamine 2, 3-dioxygenase. Rats fed with PS150 showed less inflammation and activation of hypothalamic–pituitary–adrenal. Abstract: In order to investigate novel probiotics for brain health improvement, the psychotropic potential of Lactobacillus fermentum PS150 (PS150) was evaluated using a 4-week chronic mild stress (CMS) model in rats. Rats fed with PS150 showed less anxious and depressive behaviour in EPM, OFT and FST compared with negative control rats (P < 0.05). Rats in PS150 group also showed less cognitive deficits as evaluated by MWM and NOR tests compared with negative control rats (P < 0.05). PS150 reversed the decrease of serotonin, elevation of IDO and ameliorated brain degeneration in the rat brain induced by CMS. Lowered interferon-γ gene expression and corticosterone levels in brain and plasma were observed in PS150 group compared with the negative control (P < 0.05). Taken together, PS150 prevented stress-mediated reduction of serotonin and neurodegeneration in the rat brain and helped stressed rats achieved more normal behaviour demonstrating the psychotropic potential of PS150 via the gut-brain axis.